Telemarketing in Islamic Economics: Theory and Practice - Rini Puji Astuti (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
One of the keys to success for the survival of the company's business is a marketing strategy. At present, marketing has been recognized as a means to meet customer satisfaction. The company will prioritize everything required by consumers. More precisely, companies will prioritize consumer wants, not based on what consumer needs. Therefore, companies always concern about marketing strategies to attract as many customers as possible and increase their sales. By using a qualitative descriptive approach based on library research, this paper describes telemarketing as one of the promotional strategies in the marketing concept. This paper tries to describe telemarketing in an Islamic economic perspective, based on theory and practice.